Counting rational points on algebraic varieties - Timothy Browning; Heath-Brown, Roger; Salberger, Per (Duke Mathematical Journal)
For any N ≥ 2, let Z ⊂ ℙN be a geometrically integral algebraic variety of degree d. This article is concerned with the number Nz(B) of ℚ-rational points on Z which have height at most B. For any ε > 0, we establish the estimate NZ(B) = O d,ε,N(Bdim Z+ε), provided that d ≥ 6. As indicated, the implied constant depends at most on d, ε, and N.

Sums of arithmetic functions over values of binary forms - de la Bretèche, Régis; Timothy Browning (Acta Arithmetica)
This paper is concerned with the average order of certain arithmetic functions, as they range over the values taken by binary forms.

Ground-state energy of a dilute Fermi gas - Lieb, Élliott H; Robert Seiringer; Solovej, Jan P

One-dimensional behavior of dilute, trapped Bose gases in traps - Robert Seiringer; Lieb, Élliott H; Yngvason, Jakob

Derivation of the Gross-Pitaevskii equation for rotating Bose gases - Lieb, Élliott H; Robert Seiringer (Communications in Mathematical Physics)
We prove that the Gross-Pitaevskii equation correctly describes the ground state energy and corresponding one-particle density matrix of rotating, dilute, trapped Bose gases with repulsive two-body interactions. We also show that there is 100% Bose-Einstein condensation. While a proof that the GP equation correctly describes non-rotating or slowly rotating gases was known for some time, the rapidly rotating case was unclear because the Bose (i.e., symmetric) ground state is not the lowest eigenstate of the Hamiltonian in this case. We have been able to overcome this difficulty with the aid of coherent states. Our proof also conceptually simplifies the previous proof for the slowly rotating case. In the case of axially symmetric traps, our results show that the appearance of quantized vortices causes spontaneous symmetry breaking in the ground state.

A correlation estimate for quantum many-body systems at positive temperature - Robert Seiringer (Reviews in Mathematical Physics)
We present an inequality that gives a lower bound on the expectation value of certain two-body interaction potentials in a general state on Fock space in terms of the corresponding expectation value for thermal equilibrium states of non-interacting systems and the difference in the free energy. This bound can be viewed as a rigorous version of first-order perturbation theory for many-body systems at positive temperature. As an application, we give a proof of the first two terms in a high density (and high temperature) expansion of the free energy of jellium with Coulomb interactions, both in the fermionic and bosonic case. For bosons, our method works above the transition temperature (for the non-interacting gas) for Bose-Einstein condensation.

The thermodynamic pressure of a dilute fermi gas - Robert Seiringer (Communications in Mathematical Physics)
We consider a gas of fermions with non-zero spin at temperature T and chemical potential μ. We show that if the range of the interparticle interaction is small compared to the mean particle distance, the thermodynamic pressure differs to leading order from the corresponding expression for non-interacting particles by a term proportional to the scattering length of the interparticle interaction. This is true for any repulsive interaction, including hard cores. The result is uniform in the temperature as long as T is of the same order as the Fermi temperature, or smaller.

Lieb-Thirring inequalities for Schrödinger operators with complex-valued potentials - Frank, Rupert L; Laptev, Ari; Lieb, Élliott H; Robert Seiringer (Letters in Mathematical Physics)
Inequalities are derived for power sums of the real part and the modulus of the eigenvalues of a Schrödinger operator with a complex-valued potential.

Dilute, trapped Bose gases and Bose-Einstein condensation - Robert Seiringer (Large Coulomb Systems)
The recent experimental success in creating Bose-Einstein condensates of alkali atoms, honored by the Nobel prize awards in 2001 [1,5], led to renewed interest in the mathematical description of interacting Bose gases.

Bose-Einstein condensation as a quantum phase transition in an optical lattice - Aizenman, Michael; Lieb, Élliott H; Robert Seiringer; Solovej, Jan P; Yngvason, Jakob (Mathematical Physics of Quantum Mechanics)
One of the most remarkable recent developments in the study of ultracold Bose gases is the observation of a reversible transition from a Bose Einstein condensate to a state composed of localized atoms as the strength of a periodic, optical trapping potential is varied. In [1] a model of this phenomenon has been analyzed rigorously. The gas is a hard core lattice gas and the optical lattice is modeled by a periodic potential of strength λ. For small λ and temperature Bose- Einstein condensation (BEC) is proved to occur, while at large λ BEC disappears, even in the ground state, which is a Mott-insulator state with a characteristic gap. The inter-particle interaction is essential for this effect. This contribution gives a pedagogical survey of these results.

On six problems posed by Jarik Nešetřil - Bang-Jensen, Jørgen; Reed, Bruce; Schacht, Bruce; Šámal, Robert; Toft, Bjarne; Uli Wagner (Topics in Discrete Mathematics)

Online conflict-free coloring for intervals - Chent, Ke; Fiat, Amos; Kaplan, Haim; Levy, Meital B; Matoušek, Jiří; Mossel, Elchanan; Pach, János; Sharir, Micha; Smorodinsky, Shakhar; Uli Wagner; Welzl, Emo (SIAM Journal on Computing)
We consider an online version of the conflict-free coloring of a set of points on the line, where each newly inserted point must be assigned a color upon insertion, and at all times the coloring has to be conflict-free, in the sense that in every interval I there is a color that appears exactly once in I. We present deterministic and randomized algorithms for achieving this goal, and analyze their performance, that is, the maximum number of colors that they need to use, as a function of the number n of inserted points. We first show that a natural and simple (deterministic) approach may perform rather poorly, requiring Ω(√̃) colors in the worst case. We then derive two efficient variants of this simple algorithm. The first is deterministic and uses O(log 2 n) colors, and the second is randomized and uses O(log n) colors with high probability. We also show that the O(log 2 n) bound on the number of colors used by our deterministic algorithm is tight on the worst case. We also analyze the performance of the simplest proposed algorithm when the points are inserted in a random order and present an incomplete analysis that indicates that, with high probability, it uses only O(log n) colors. Finally, we show that in the extension of this problem to two dimensions, where the relevant ranges are disks, n colors may be required in the worst case.

On a geometric generalization of the Upper Bound Theorem - Uli Wagner
We prove an upper bound, tight up to a factor of 2, for the number of vertices of level at most t in an arrangement of n halfspaces in R , for arbitrary n and d (in particular, the dimension d is not considered constant). This partially settles a conjecture of Eckhoff, Linhart, and Welzl. Up to the factor of 2, the result generalizes McMullen's Upper Bound Theorem for convex polytopes (the case ℓ = O) and extends a theorem of Linhart for the case d ≤ 4. Moreover, the bound sharpens asymptotic estimates obtained by Clarkson and Shor. The proof is based on the h-matrix of the arrangement (a generalization, introduced by Mulmuley, of the h-vector of a convex polytope). We show that bounding appropriate sums of entries of this matrix reduces to a lemma about quadrupels of sets with certain intersection properties, and we prove this lemma, up to a factor of 2, using tools from multilinear algebra. This extends an approach of Alon and Kalai, who used linear algebra methods for an alternative proof of the classical Upper Bound Theorem. The bounds for the entries of the h-matrix also imply bounds for the number of i-dimensional faces, i > 0, at level at most ℓ. Furthermore, we discuss a connection with crossing numbers of graphs that was one of the main motivations for investigating exact bounds that are valid for arbitrary dimensions.

K-sets in four dimensions - Matoušek, Jiří; Sharir, Micha; Smorodinsky, Shakhar; Uli Wagner (Discrete & Computational Geometry)
We show, with an elementary proof, that the number of halving simplices in a set of n points in 4 in general position is O(n4-2/45). This improves the previous bound of O(n4-1/134). Our main new ingredient is a bound on the maximum number of halving simplices intersecting a fixed 2-plane.

Differential localization and regulation of stargazin-like protein, γ-8 and stargazin in the plasma membrane of hippocampal and cortical neurons - Inamura, Mihoko; Itakura, Makoto; Okamoto, Hirotsugu; Hoka, Sumio; Mizoguchi, Akira; Fukazawa, Yugo; Ryuichi Shigemoto; Yamamori, Saori; Takahashi, Masami (Neuroscience Research)
Transmembrane AMPA receptor regulatory proteins (TARPs), including stargazin/γ-2, are associated with AMPA receptors and participate in their surface delivery and anchoring at the postsynaptic membrane. TARPs may also act as a positive modulator of the AMPA receptor ion channel function; however, little is known about other TARP members except for stargazin/γ-2. We examined the synaptic localization of stargazin/γ-2 and γ-8 by immunoelectron microscopy and biochemical analysis. The analysis of sodium dodecyl sulfate-digested freeze-fracture replica labeling revealed that stargazin/γ-2 was concentrated in the postsynaptic area, whereas γ-8 was distributed both in synaptic and extra-synaptic plasma membranes of the hippocampal neuron. When a synaptic plasma membrane-enriched brain fraction was treated with Triton X-100 and separated by sucrose density gradient ultracentrifugation, a large proportion of NMDA receptor and stargazin/γ-2 was accumulated in raft-enriched fractions, whereas AMPA receptor and γ-8 were distributed in both the raft-enriched fractions and other Triton-insoluble fractions. Phosphorylation of stargazin/γ-2 and γ-8 was regulated by different sets of kinases and phosphatases in cultured cortical neurons. These results suggested that stargazin/γ-2 and γ-8 have distinct roles in postsynaptic membranes under the regulation of different intracellular signaling pathways.

Localization of metabotropic GABA receptor subunits GABAB1 and GABAB2 relative to synaptic sites in the rat developing cerebellum - Luján, Rafael; Ryuichi Shigemoto (European Journal of Neuroscience)
The highest densities of the two metabotropic GABA subunits, GABA B1 and GABAB2, have been reported as occurring around the glutamatergic synapses between Purkinje cell spines and parallel fibre varicosities. In order to determine how this distribution is achieved during development, we investigated the expression pattern and the cellular and subcellular localization of the GABAB1 and GABAB2 subunits in the rat cerebellum during postnatal development. At the light microscopic level, immunoreactivity for the GABAB1 and GABAB2 subunits was very prominent in the developing molecular layer, especially in Purkinje cells. Using double immunofluorescence, we demonstrated that GABAB1 was transiently expressed in glial cells. At the electron microscopic level, immunoreactivity for GABAB receptors was always detected both pre- and postsynaptically. Presynaptically, GABAB1 and GABAB2 were localized in the extrasynaptic membrane of parallel fibres at all ages, and only rarely in GABAergic axons. Postsynaptically, GABAB receptors were localized to the extrasynaptic and perisynaptic plasma membrane of Purkinje cell dendrites and spines throughout development. Quantitative analysis and three-dimensional reconstructions further revealed a progressive developmental movement of the GABAB1 subunit on the surface of Purkinje cells from dendritic shafts to its final destination, the dendritic spines. Together, these results indicate that GABAB receptors undergo dynamic regulation during cerebellar development in association with the establishment and maturation of glutamatergic synapses to Purkinje cells.

A CaV2.1 calcium channel mutation rocker reduces the number of postsynaptic AMPA receptors in parallel fiber-Purkinje cell synapses - Kodama, Takashi; Itsukaichi-Nishida, Yuko; Fukazawa, Yugo; Wakamori, Minoru; Miyata, Mariko; Molnár, Elek; Mori, Yasuo; Ryuichi Shigemoto; Imoto, Keiji (European Journal of Neuroscience)
The rocker mice are hereditary ataxic mutants that carry a point mutation in the gene encoding the CaV2.1 (P/Q-type) Ca2+ channel α1 subunit, and show the mildest symptoms among the reported CaV2.1 mutant mice. We studied the basic characteristics of the rocker mutant Ca2+ channel and their impacts on excitatory synaptic transmission in cerebellar Purkinje cells (PCs). In acutely dissociated PC somas, the rocker mutant channel showed a moderate reduction in Ca2+ channel current density, whereas its kinetics and voltage dependency of gating remained nearly normal. Despite the small changes in channel function, synaptic transmission in the parallel fiber (PF)-PC synapses was severely impaired. The climbing fiber inputs onto PCs showed a moderate impairment but could elicit normal complex spikes. Presynaptic function of the PF-PC synapses, however, was unexpectedly almost normal in terms of paired-pulse facilitation, sensitivity to extracellular Ca2+ concentration and glutamate concentration in synaptic clefts. Electron microscopic analyses including freeze-fracture replica labeling revealed that both the number and density of postsynaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors substantially decreased without gross structural changes of the PF-PC synapses. We also observed an abnormal arborization of PC dendrites in young adult rocker mice (∼ 1 month old). These lines of evidence suggest that even a moderate dysfunction of CaV2.1 Ca2+ channel can cause substantial changes in postsynaptic molecular composition of the PF-PC synapses and dendritic structure of PCs.

Differential Compartmentalization and Distinct Functions of GABAB Receptor Variants - Vigot, Réjan; Barbieri, Samuel; Bräuner-Osborne, Hans; Tureček, Rostislav; Ryuichi Shigemoto; Zhang, Yan Ping; Luján, Rafael; Jacobson, Laura H; Biermann, Barbara; Fritschy, Jean-Marc; Vacher, Claire-Marie; Müller, Matthias P; et al. (Neuron)
GABAB receptors are the G protein-coupled receptors for the main inhibitory neurotransmitter in the brain, γ-aminobutyric acid (GABA). Molecular diversity in the GABAB system arises from the GABAB1a and GABAB1b subunit isoforms that solely differ in their ectodomains by a pair of sushi repeats that is unique to GABAB1a. Using a combined genetic, physiological, and morphological approach, we now demonstrate that GABAB1 isoforms localize to distinct synaptic sites and convey separate functions in vivo. At hippocampal CA3-to-CA1 synapses, GABAB1a assembles heteroreceptors inhibiting glutamate release, while predominantly GABAB1b mediates postsynaptic inhibition. Electron microscopy reveals a synaptic distribution of GABAB1 isoforms that agrees with the observed functional differences. Transfected CA3 neurons selectively express GABAB1a in distal axons, suggesting that the sushi repeats, a conserved protein interaction motif, specify heteroreceptor localization. The constitutive absence of GABAB1a but not GABAB1b results in impaired synaptic plasticity and hippocampus-dependent memory, emphasizing molecular differences in synaptic GABAB functions.

Compartment-dependent colocalization of Kir3.2-containing K+ channels and GABAB receptors in hippocampal pyramidal cells - Kulik, Ákos; Vida, Imre; Fukazawa, Yugo; Guetg, Nicole; Kasugai, Yu; Marker, Cheryl L; Rigato, Franck; Bettler, Bernhard; Wickman, Kevin D; Frotscher, Michael; Ryuichi Shigemoto (Journal of Neuroscience)
G-protein-coupled inwardly rectifying K+ channels (Kir3 channels) coupled to metabotropic GABAB receptors are essential for the control of neuronal excitation. To determine the distribution of Kir3 channels and their spatial relationship to GABAB receptors on hippocampal pyramidal cells, we used a high-resolution immunocytochemical approach. Immunoreactivity for the Kir3.2 subunit was most abundant postsynaptically and localized to the extrasynaptic plasma membrane of dendritic shafts and spines of principal cells. Quantitative analysis of immunogold particles for Kir3.2 revealed an enrichment of the protein around putative glutamatergic synapses on dendritic spines, similar to that of GABA B1. Consistent with this observation, a high degree of coclustering of Kir3.2 and GABAB1 was revealed around excitatory synapses by the highly sensitive SDS-digested freeze-fracture replica immunolabeling. In contrast, in dendritic shafts receptors and channels were found to be mainly segregated. These results suggest that Kir3.2-containing K+ channels on dendritic spines preferentially mediate the effect of GABA, whereas channels on dendritic shafts are likely to be activated by other neurotransmitters as well. Thus, Kir3 channels, localized to different subcellular compartments of hippocampal principal cells, appear to be differentially involved in synaptic integration in pyramidal cell dendrites.

Generalization of amygdala LTP and conditioned fear in the absence of presynaptic inhibition - Shaban, Hamdy; Humeau, Yann; Herry, Cyril; Cassasus, Guillaume; Ryuichi Shigemoto; Ciocchi, Stéphane; Barbieri, Samuel; Van Der Putten, Herman V; Kaupmann, Klemens; Bettler, Bernhard; Lüthi, Andreas (Nature Neuroscience)
Pavlovian fear conditioning, a simple form of associative learning, is thought to involve the induction of associative, NMDA receptor-dependent long-term potentiation (LTP) in the lateral amygdala. Using a combined genetic and electrophysiological approach, we show here that lack of a specific GABAB receptor subtype, GABAB(1a,2), unmasks a nonassociative, NMDA receptor-independent form of presynaptic LTP at cortico-amygdala afferents. Moreover, the level of presynaptic GABA B(1a,2) receptor activation, and hence the balance between associative and nonassociative forms of LTP, can be dynamically modulated by local inhibitory activity. At the behavioral level, genetic loss of GABA B(1a) results in a generalization of conditioned fear to nonconditioned stimuli. Our findings indicate that presynaptic inhibition through GABAB(1a,2) receptors serves as an activity-dependent constraint on the induction of homosynaptic plasticity, which may be important to prevent the generalization of conditioned fear.

Metabotropic glutamate receptors - Ferraguti, Francesco; Ryuichi Shigemoto (Cell and Tissue Research)
Metabotropic glutamate receptors (mGlus) are a family of G-protein-coupled receptors activated by the neurotransmitter glutamate. Molecular cloning has revealed eight different subtypes (mGlu1-8) with distinct molecular and pharmacological properties. Multiplicity in this receptor family is further generated through alternative splicing. mGlus activate a multitude of signalling pathways important for modulating neuronal excitability, synaptic plasticity and feedback regulation of neurotransmitter release. In this review, we summarize anatomical findings (from our work and that of other laboratories) describing their distribution in the central nervous system. Recent evidence regarding the localization of these receptors in peripheral tissues will also be examined. The distinct regional, cellular and subcellular distribution of mGlus in the brain will be discussed in view of their relationship to neurotransmitter release sites and of possible functional implications.

Derivation of the Gross-Pitaevskii hierarchy for the dynamics of Bose-Einstein condensate - László Erdös; Schlein, Benjamin; Yau, Horng-Tzer (Communications on Pure and Applied Mathematics)
Consider a system of N bosons on the three-dimensional unit torus interacting via a pair potential N 2V(N(x i - x j)) where x = (x i, . . ., x N) denotes the positions of the particles. Suppose that the initial data ψ N,0 satisfies the condition 〈ψ N,0, H 2 Nψ N,0) ≤ C N 2 where H N is the Hamiltonian of the Bose system. This condition is satisfied if ψ N,0 = W Nφ N,t where W N is an approximate ground state to H N and φ N,0 is regular. Let ψ N,t denote the solution to the Schrödinger equation with Hamiltonian H N. Gross and Pitaevskii proposed to model the dynamics of such a system by a nonlinear Schrödinger equation, the Gross-Pitaevskii (GP) equation. The GP hierarchy is an infinite BBGKY hierarchy of equations so that if u t solves the GP equation, then the family of k-particle density matrices ⊗ k |u t?〉 〈 t | solves the GP hierarchy. We prove that as N → ∞ the limit points of the k-particle density matrices of ψ N,t are solutions of the GP hierarchy. Our analysis requires that the N-boson dynamics be described by a modified Hamiltonian that cuts off the pair interactions whenever at least three particles come into a region with diameter much smaller than the typical interparticle distance. Our proof can be extended to a modified Hamiltonian that only forbids at least n particles from coming close together for any fixed n.

Gross-Pitaevskii equation as the mean field limit of weakly coupled bosons - Elgart, Alexander; László Erdös; Schlein, Benjamin; Yau, Horng-Tzer (Archive for Rational Mechanics and Analysis)
We consider the dynamics of N boson systems interacting through a pair potential N -1 V a (x i -x j ) where V a (x)=a -3 V(x/a). We denote the solution to the N-particle Schrödinger equation by Ψ N, t . Recall that the Gross-Pitaevskii (GP) equation is a nonlinear Schrödinger equation and the GP hierarchy is an infinite BBGKY hierarchy of equations so that if u t solves the GP equation, then the family of k-particle density matrices [InlineMediaObject not available: see fulltext.] solves the GP hierarchy. Under the assumption that a = Nε for 0 < ε < 3/5, we prove that as N→∞ the limit points of the k-particle density matrices of Ψ N, t are solutions of the GP hierarchy with the coupling constant in the nonlinear term of the GP equation given by ∫ V (x)dx. The uniqueness of the solutions of this hierarchy remains an open question.

Towards the quantum Brownian motion - László Erdös; Salmhofer, Manfred; Yau, Horng-Tzer
We consider random Schrödinger equations on Rd or Zd for d ≥ 3 with uncorrelated, identically distributed random potential. Denote by λ the coupling constant and ψt the solution with initial data ψ0.

Finite lifetime of turbulence in shear flows - Björn Hof; Westerweel, Jerry; Schneider, Tobias M; Eckhardt, Bruno (Nature)
Generally, the motion of fluids is smooth and laminar at low speeds but becomes highly disordered and turbulent as the velocity increases. The transition from laminar to turbulent flow can involve a sequence of instabilities in which the system realizes progressively more complicated states, or it can occur suddenly. Once the transition has taken place, it is generally assumed that, under steady conditions, the turbulent state will persist indefinitely. The flow of a fluid down a straight pipe provides a ubiquitous example of a shear flow undergoing a sudden transition from laminar to turbulent motion. Extensive calculations and experimental studies have shown that, at relatively low flow rates, turbulence in pipes is transient, and is characterized by an exponential distribution of lifetimes. They also suggest that for Reynolds numbers exceeding a critical value the lifetime diverges (that is, becomes infinitely large), marking a change from transient to persistent turbulence. Here we present experimental data and numerical calculations covering more than two decades of lifetimes, showing that the lifetime does not in fact diverge but rather increases exponentially with the Reynolds number. This implies that turbulence in pipes is only a transient event (contrary to the commonly accepted view), and that the turbulent and laminar states remain dynamically connected, suggesting avenues for turbulence control.

Observation of nonlinear travelling waves in turbulent pipe flow - Björn Hof; van Doorne, Casimir W; Westerweel, Jerry; Nieuwstadt, Frans T (Fluid Mechanics and its Applications)
Transition to turbulence in pipe flow has posed a riddle in fluid dynamics since the pioneering experiments of Reynolds[1]. Although the laminar flow is linearly stable for all flow rates, practical pipe flows become turbulent at large enough flow speeds. Turbulence arises suddenly and fully without distinct steps and without a clear critical point. The complexity of this problem has puzzled mathematicians, physicists and engineers for more than a century and no satisfactory explanation of this problem has been given. In a very recent theoretical approach it has been suggested that unstable solutions of the Navier Stokes equations may hold the key to understanding this problem. In numerical studies such unstable states have been identified as exact solutions for the idealized case of a pipe with periodic boundary conditions[2, 3]. These solutions have the form of waves extending through the entire pipe and travelling in the streamwise direction at a phase speed close to the bulk velocity of the fluid. With the aid of a recently developed high-speed stereoscopic Particle Image Velocimetry (PIV) system, we were able to observe transients of such unstable solutions in turbulent pipe flow[4].

Stochastic Monoallelic Expression of IL 10 in T Cells - Calado, Dinis P; Tiago Paixao; Holmberg, Dan; Haury, Matthias (Journal of Immunology)
IL-10 is a potent anti-inflammatory and immunomodulatory cytokine, exerting major effects in the degree and quality of the immune response. Using a newly generated IL-10 reporter mouse model, which easily allows the study of IL-10 expression from each allele in a single cell, we report here for the first time that IL-10 is predominantly monoallelic expressed in CD4+ T cells. Furthermore, we have compelling evidence that this expression pattern is not due to parental imprinting, allelic exclusion, or strong allelic bias. Instead, our results support a stochastic regulation mechanism, in which the probability to initiate allelic transcription depends on the strength of TCR signaling and subsequent capacity to overcome restrictions imposed by chromatin hypoacetylation. In vivo Ag-experienced T cells show a higher basal probability to transcribe IL-10 when compared with naive cells, yet still show mostly monoallelic IL-10 expression. Finally, statistical analysis on allelic expression data shows transcriptional independence between both alleles. We conclude that CD4+ T cells have a low probability for IL-10 allelic activation resulting in a predominantly monoallelic expression pattern, and that IL-10 expression appears to be stochastically regulated by controlling the frequency of expressing cells, rather than absolute protein levels per cell.

Graph cut algorithms for binocular stereo with occlusions - Vladimir Kolmogorov; Zabih, Ramin (Handbook of Mathematical Models in Computer Vision)
Most binocular stereo algorithms assume that all scene elements are visible from both cameras. Scene elements that are visible from only one camera, known as occlusions, pose an important challenge for stereo. Occlusions are important for segmentation, because they appear near discontinuities. However, stereo algorithms tend to ignore occlusions because of their difficulty. One reason is that occlusions require the input images to be treated symmetrically, which complicates the problem formulation. Worse, certain depth maps imply physically impossible scene configurations, and must be excluded from the output. In this chapter we approach the problem of binocular stereo with occlusions from an energy minimization viewpoint. We begin by reviewing traditional stereo methods that do not handle occlusions. If occlusions are ignored, it is easy to formulate the stereo problem as a pixel labeling problem, which leads to an energy function that is common in early vision. This kind of energy function can he minimized using graph cuts, which is a combinatorial optimization technique that has proven to be very effective for low-level vision problems. Motivated by this, we have designed two graph cut stereo algorithms that are designed to handle occlusions. These algorithms produce promising experimental results on real data with ground truth.

In vitro culture of Arabidopsis embryos - Sauer, Michael; Jirí Friml (Somatic Embryogenesis)
Arabidopsis thaliana is currently the most important model organism for basic molecular plant research. It is also a favourable model for developmental biology, as its embryogenesis follows a nearly invariant pattern of cell divisions and cell type specifications. Study of embryogenesis can involve genetic, physiological or biochemical approaches, but is always limited by the inaccessibility of the embryos which develop deep inside maternal tissue. Thus, for developmental studies, there is an increasing demand for methods which allow embryogenesis under artificial conditions, providing better accessibility to experimental manipulation. In this chapter, we address theoretical aspects of embryo culture, give some thoughts on which embryo culture system is suited best for which application and finally discuss three current methods which have been successfully used in Arabidopsis embryo culture. © 2006 Springer-Verlag Berlin Heidelberg.

PIN proteins perform a rate-limiting function in cellular auxin efflux - Petrášek, Jan; Mravec, Jozef; Bouchard, Rodolphe; Blakeslee, Joshua; Melinda Abas; Seifertová, Daniela; Wiśniewska, Justyna; Tadele, Zerihun; Kubeš, Martin; Čovanová, Milada; Dhonukshe, Pankaj; Skůpa, Petr; et al. (Science)
Intercellular flow of the phytohormone auxin underpins multiple developmental processes in plants. Plant-specific pin-formed (PIN) proteins and several phosphoglycoprotein (PGP) transporters are crucial factors in auxin transport-related development, yet the molecular function of PINs remains unknown. Here, we show that PINs mediate auxin efflux from mammalian and yeast cells without needing additional plant-specific factors. Conditional gain-of-function alleles and quantitative measurements of auxin accumulation in Arabidopsis and tobacco cultured cells revealed that the action of PINs in auxin efflux is distinct from PGP, rate-limiting, specific to auxins, and sensitive to auxin transport inhibitors. This suggests a direct involvement of PINs in catalyzing cellular auxin efflux.

Control of leaf vascular patterning by polar auxin transport - Scarpella, Enrico; Marcos, Danielle; Jirí Friml; Berleth, Thomas (Genes and Development)
The formation of the leaf vascular pattern has fascinated biologists for centuries. In the early leaf primordium, complex networks of procambial cells emerge from homogeneous subepidermal tissue. The molecular nature of the underlying positional information is unknown, but various lines of evidence implicate gradually restricted transport routes of the plant hormone auxin in defining sites of procambium formation. Here we show that a crucial member of the AtPIN family of auxin-efflux-associated proteins, AtPIN1, is expressed prior to pre-procambial and procambial cell fate markers in domains that become restricted toward sites of procambium formation. Subcellular AtPIN1 polarity indicates that auxin is directed to distinct "convergence points" in the epidermis, from where it defines the positions of major veins. Integrated polarities in all emerging veins indicate auxin drainage toward pre-existing veins, but veins display divergent polarities as they become connected at both ends. Auxin application and transport inhibition reveal that convergence point positioning and AtPIN1 expression domain dynamics are self-organizing, auxin-transport-dependent processes. We derive a model for self-regulated, reiterative patterning of all vein orders and postulate at its onset a common epidermal auxin-focusing mechanism for major-vein positioning and phyllotactic patterning.

Intracellular trafficking and proteolysis of the Arabidopsis auxin-efflux facilitator PIN2 are involved in root gravitropism - Abas, Lindy; Benjamins, René; Malenica, Nenad; Paciorek, Tomasz; Wiśniewska, Justyna; Moulinier-Anzola, Jeanette C; Sieberer, Tobias; Jirí Friml; Luschnig, Christian (Nature Cell Biology)
Root gravitropism describes the orientation of root growth along the gravity vector and is mediated by differential cell elongation in the root meristem. This response requires the coordinated, asymmetric distribution of the phytohormone auxin within the root meristem, and depends on the concerted activities of PIN proteins and AUX1 - members of the auxin transport pathway. Here, we show that intracellular trafficking and proteasome activity combine to control PIN2 degradation during root gravitropism. Following gravi-stimulation, proteasome-dependent variations in PIN2 localization and degradation at the upper and lower sides of the root result in asymmetric distribution of PIN2. Ubiquitination of PIN2 occurs in a proteasome-dependent manner, indicating that the proteasome is involved in the control of PIN2 turnover. Stabilization of PIN2 affects its abundance and distribution, and leads to defects in auxin distribution and gravitropic responses. We describe the effects of auxin on PIN2 localization and protein levels, indicating that redistribution of auxin during the gravitropic response may be involved in the regulation of PIN2 protein.

Endocytosis of cell surface material mediates cell plate formation during plant cytokinesis - Dhonukshe, Pankaj; Baluška, František; Schlicht, Markus; Hlavacka, Andrej; Šamaj, Jozef; Jirí Friml; Gadella, Theodorus W (Developmental Cell)
Dividing plant cells perform a remarkable task of building a new cell wall within the cytoplasm in a few minutes. A long-standing paradigm claims that this primordial cell wall, known as the cell plate, is generated by delivery of newly synthesized material from Golgi apparatus-originated secretory vesicles. Here, we show that, in diverse plant species, cell surface material, including plasma membrane proteins, cell wall components, and exogenously applied endocytic tracers, is rapidly delivered to the forming cell plate. Importantly, this occurs even when de novo protein synthesis is blocked. In addition, cytokinesis-specific syntaxin KNOLLE as well as plasma membrane (PM) resident proteins localize to endosomes that fuse to initiate the cell plate. The rate of endocytosis is strongly enhanced during cell plate formation, and its genetic or pharmacological inhibition leads to cytokinesis defects. Our results reveal that endocytic delivery of cell surface material significantly contributes to cell plate formation during plant cytokinesis.

Polar PIN localization directs auxin flow in plants - Wiśniewska, Justyna; Xu, Jian; Seifertová, Daniela; Brewer, Philip B; Růžička, Kamil; Blilou, Ikram; Rouquié, David; Eva Benková; Scheres, Ben; Jirí Friml (Science)
Polar flow of the phytohormone auxin requires plasma membrane‐associated PIN proteins and underlies multiple developmental processes in plants. Here we address the importance of the polarity of subcellular PIN localization for the directionality of auxin transport in Arabidopsis thaliana. Expression of different PINs in the root epidermis revealed the importance of PIN polar positions for directional auxin flow and root gravitropic growth. Interfering with sequence-embedded polarity signals directly demonstrates that PIN polarity is a primary factor in determining the direction of auxin flow in meristematic tissues. This finding provides a crucial piece in the puzzle of how auxin flow can be redirected via rapid changes in PIN polarity.

Apical-basal polarity: Why plant cells don't stand on their heads - Friml, Jirí; Benfey, Philip; Benková, Eva; Bennett, Malcolm; Berleth, Thomas; Geldner, Niko; Grebe, Markus; Heisler, Marcus; Hejátko, Jan; Jürgens, Gerd; Laux, Thomas; Lindsey, Keith; et al. (Trends in Plant Science)

A molecular framework for plant regeneration - Xu, Jian; Hofhuis, Hugo; Heidstra, Renze; Sauer, Michael; Jirí Friml; Scheres, Ben (Science)
Plants and some animals have a profound capacity to regenerate organs from adult tissues. Molecular mechanisms for regeneration have, however, been largely unexplored. Here we investigate a local regeneration response in Arabidopsis roots. Laser-induced wounding disrupts the flow of auxin-a cell-fate-instructive plant hormone-in root tips, and we demonstrate that resulting cell-fate changes require the PLETHORA, SHORTROOT, and SCARECROW transcription factors. These transcription factors regulate the expression and polar position of PIN auxin efflux-facilitating membrane proteins to reconstitute auxin transport in renewed root tips. Thus, a regeneration mechanism using embryonic root stem-cell patterning factors first responds to and subsequently stabilizes a new hormone distribution.

Auxin signaling - Paciorek, Tomasz; Friml, Jirí (Journal of Cell Science)

Canalization of auxin flow by Aux/IAA-ARF-dependent feedback regulation of PIN polarity - Sauer, Michael; Balla, Jozef; Luschnig, Christian; Wiśniewska, Justyna; Reinöhl, Vilém; Friml, Jirí; Benková, Eva (Genes and Development)
Plant development is characterized by a profound ability to regenerate and form tissues with new axes of polarity. An unsolved question concerns how the position within a tissue and cues from neighboring cells are integrated to specify the polarity of individual cells. The canalization hypothesis proposes a feedback effect of the phytohormone auxin on the directionality of intercellular auxin flow as a means to polarize tissues. Here we identify a cellular and molecular mechanism for canalization. Local auxin application, wounding, or auxin accumulation during de novo organ formation lead to rearrangements in the subcellular polar localization of PIN auxin transport components. This auxin effect on PIN polarity is cell-specific, does not depend on PIN transcription, and involves the Aux/IAA-ARF (indole-3-acetic acid-auxin response factor) signaling pathway. Our data suggest that auxin acts as polarizing cue, which links individual cell polarity with tissue and organ polarity through control of PIN polar targeting. This feedback regulation provides a conceptual framework for polarization during multiple regenerative and patterning processes in plants.

Spatiotemporal asymmetric auxin distribution: A means to coordinate plant development - Tanaka, Hirokazu; Dhonukshe, Pankaj; Brewer, Philip; Friml, Jirí (Cellular and Molecular Life Sciences)
The plant hormone auxin plays crucial roles in regulating plant growth development, including embryo and root patterning, organ formation, vascular tissue differentiation and growth responses to environmental stimuli. Asymmetric auxin distribution patterns have been observed within tissues, and these so-called auxin gradients change dynamically during different developmental processes. Most auxin is synthesized in the shoot and distributed directionally throughout the plant. This polar auxin transport is mediated by auxin influx and efflux facilitators, whose subcellular polar localizations guide the direction of auxin flow. The polar localization of PIN auxin efflux carriers changes in response to developmental and external cues in order to channel auxin flow in a regulated manner for organized growth. Auxin itself modulates the expression and subcellular localization of PIN proteins, contributing to a complex pattern of feedback regulation. Here we review the available information mainly from studies of a model plant, Arabidopsis thaliana, on the generation of auxin gradients, the regulation of polar auxin transport and further downstream cellular events.

Subcellular trafficking of the Arabidopsis auxin influx carrier AUX1 uses a novel pathway distinct from PIN1 - Kleine-Vehn, Jürgen; Dhonukshe, Pankaj; Swarup, Ranjan; Bennett, Malcolm; Jirí Friml (Plant Cell)
The directional flow of the plant hormone auxin mediates multiple developmental processes, including patterning and tropisms. Apical and basal plasma membrane localization of AUXIN-RESISTANT1 (AUX1) and PIN-FORMED1 (PIN1) auxin transport components underpins the directionality of intercellular auxin flow in Arabidopsis thaliana roots. Here, we examined the mechanism of polar trafficking of AUX1. Real-time live cell analysis along with subcellular markers revealed that AUX1 resides at the apical plasma membrane of protophloem cells and at highly dynamic subpopulations of Golgi apparatus and endosomes in all cell types. Plasma membrane and intracellular pools of AUX1 are interconnected by actin-dependent constitutive trafficking, which is not sensitive to the vesicle trafficking inhibitor brefeldin A. AUX1 subcellular dynamics are not influenced by the auxin influx inhibitor NOA but are blocked by the auxin efflux inhibitors TIBA and PBA. Furthermore, auxin transport inhibitors and interference with the sterol composition of membranes disrupt polar AUX1 distribution at the plasma membrane. Compared with PIN1 trafficking, AUX1 dynamics display different sensitivities to trafficking inhibitors and are independent of the endosomal trafficking regulator ARF GEF GNOM. Hence, AUX1 uses a novel trafficking pathway in plants that is distinct from PIN trafficking, providing an additional mechanism for the fine regulation of auxin transport.

In situ hybridization technique for mRNA detection in whole mount Arabidopsis samples - Hejátko, Jan; Blilou, Ikram; Brewer, Philip B; Jirí Friml; Scheres, Ben; Eva Benková (Nature Protocols)
High throughput microarray transcription analyses provide us with the expression profiles for large amounts of plant genes. However, their tissue and cellular resolution is limited. Thus, for detailed functional analysis, it is still necessary to examine the expression pattern of selected candidate genes at a cellular level. Here, we present an in situ mRNA hybridization method that is routinely used for the analysis of plant gene expression patterns. The protocol is optimized for whole mount mRNA localizations in Arabidopsis seedling tissues including embryos, roots, hypocotyls and young primary leaves. It can also be used for comparable tissues in other species. Part of the protocol can also be automated and performed by a liquid handling robot. Here we present a detailed protocol, recommended controls and troubleshooting, along with examples of several applications. The total time to carry out the entire procedure is ∼7 d, depending on the tissue used.

Immunocytochemical techniques for whole mount in situ protein localization in plants - Sauer, Michael; Paciorek, Tomasz; Eva Benková; Jirí Friml (Nature Protocols)
As the field of plant molecular biology is swiftly advancing, a need has been created for methods that allow rapid and reliable in situ localization of proteins in plant cells. Here we describe a whole-mount 'immunolocalization' technique for various plant tissues, including roots, hypocotyls, cotyledons, young primary leaves and embryos of Arabidopsis thaliana and other species. The detailed protocol, recommended controls and troubleshooting are presented, along with examples of applications. The protocol consists of five main procedures: tissue fixation, tissue permeation, blocking, primary and secondary antibody incubation. Notably, the first procedure (tissue fixation) includes several steps (4-12) that are absolutely necessary for protein localization in hypocotyls, cotyledons and young primary leaves but should be omitted for other tissues. The protocol is usually done in 3 days, but could also be completed in 2 days.

Immunocytochemical technique for protein localization in sections of plant tissues - Paciorek, Tomasz; Sauer, Michael; Balla, Jozef; Wiśniewska, Justyna; Jirí Friml (Nature Protocols)
There is a growing demand for methods that allow rapid and reliable in situ localization of proteins in plant cells. The immunocytochemistry protocol presented here can be used routinely to observe protein localization patterns in tissue sections of various plant species. This protocol is especially suitable for plant species with more-complex tissue architecture (such as maize, Zea mays), which makes it difficult to use an easier whole-mount procedure for protein localization. To facilitate the antibody-antigen reaction, it is necessary to include a wax-embedding and tissue-sectioning step. The protocol consists of the following procedures: chemical fixation of tissue, dehydration, wax embedding, sectioning, dewaxing, rehydration, blocking and antibody incubation. The detailed protocol, recommended controls and troubleshooting are presented here, along with examples of applications.

In situ hybridization for mRNA detection in Arabidopsis tissue sections - Brewer, Philip B; Heisler, Marcus G; Hejátko, Jan; Jirí Friml; Eva Benková (Nature Protocols)
Plant biology is currently confronted with an overflow of expression profile data provided by high-throughput microarray transcription analyses. However, the tissue and cellular resolution of these techniques is limited. Thus, it is still necessary to examine the expression pattern of selected candidate genes at a cellular level. Here we present an in situ mRNA hybridization method that is routinely used in the analysis of gene expression patterns. The protocol is optimized for mRNA localizations in sectioned tissue of Arabidopsis seedlings including embryos, roots, hypocotyls, young primary leaves and flowers. The detailed protocol, recommended controls and troubleshooting are presented along with examples of application. The total time for the process is 10 days.

In vivo migration A germ cell perspective - Kunwar, Prabhat S; Daria Siekhaus; Lehmann, Ruth (Annual Review of Cell and Developmental Biology)
The basic concepts of the molecular machinery that mediates cell migration have been gleaned from cell culture systems. However, the three-dimensional environment within an organism presents migrating cells with a much greater challenge. They must move between and among other cells while interpreting multiple attractive and repulsive cues to choose their proper path. They must coordinate their cell adhesion with their surroundings and know when to start and stop moving. New insights into the control of these remaining mysteries have emerged from genetic dissection and live imaging of germ cell migration in Drosophila, zebrafish, and mouse embryos. In this review, we first describe germ cell migration in cellular and mechanistic detail in these different model systems. We then compare these systems to highlight the emerging principles. Finally, we contrast the migration of germ cells with that of immune and cancer cells to outline the conserved and different mechanisms.

Bilayer segmentation of live video - Criminisi, Antonio; Cross, Geoffrey; Blake, Andrew; Vladimir Kolmogorov
This paper presents an algorithm capable of real-time separation of foreground from background in monocular video sequences. Automatic segmentation of layers from colour/contrast or from motion alone is known to be error-prone. Here motion, colour and contrast cues are probabilistically fused together with spatial and temporal priors to infer layers accurately and efficiently. Central to our algorithm is the fact that pixel velocities are not needed, thus removing the need for optical flow estimation, with its tendency to error and computational expense. Instead, an efficient motion vs non-motion classifier is trained to operate directly and jointly on intensity-change and contrast. Its output is then fused with colour information. The prior on segmentation is represented by a second order, temporal, Hidden Markov Model, together with a spatial MRF favouring coherence except where contrast is high. Finally, accurate layer segmentation and explicit occlusion detection are efficiently achieved by binary graph cut. The segmentation accuracy of the proposed algorithm is quantitatively evaluated with respect to existing ground-truth data and found to be comparable to the accuracy of a state of the art stereo segmentation algorithm. Fore-ground/background segmentation is demonstrated in the application of live background substitution and shown to generate convincingly good quality composite video.

Convergent tree reweighted message passing for energy minimization - Vladimir Kolmogorov (IEEE Transactions on Pattern Analysis and Machine Intelligence)
Algorithms for discrete energy minimization are of fundamental importance in computer vision. In this paper, we focus on the recent technique proposed by Wainwright et al. (Nov. 2005)- tree-reweighted max-product message passing (TRW). It was inspired by the problem of maximizing a lower bound on the energy. However, the algorithm is not guaranteed to increase this bound - it may actually go down. In addition, TRW does not always converge. We develop a modification of this algorithm which we call sequential tree-reweighted message passing. Its main property is that the bound is guaranteed not to decrease. We also give a weak tree agreement condition which characterizes local maxima of the bound with respect to TRW algorithms. We prove that our algorithm has a limit point that achieves weak tree agreement. Finally, we show that, our algorithm requires half as much memory as traditional message passing approaches. Experimental results demonstrate that on certain synthetic and real problems, our algorithm outperforms both the ordinary belief propagation and tree-reweighted algorithm in (M. J. Wainwright, et al., Nov. 2005). In addition, on stereo problems with Potts interactions, we obtain a lower energy than graph cuts.

Cosegmentation of image pairs by histogram matching - Incorporating a global constraint into MRFs - Rother, Carsten; Vladimir Kolmogorov; Minka, Thomas P; Blake, Andrew
We introduce the term cosegmentation which denotes the task of segmenting simultaneously the common parts of an image pair. A generative model for cosegmentation is presented. Inference in the model leads to minimizing an energy with an MRF term encoding spatial coherency and a global constraint which attempts to match the appearance histograms of the common parts. This energy has not been proposed previously and its optimization is challenging and NP-hard. For this problem a novel optimization scheme which we call trust region graph cuts is presented. We demonstrate that this framework has the potential to improve a wide range of research: Object driven image retrieval, video tracking and segmentation, and interactive image editing. The power of the framework lies in its generality, the common part can be a rigid/non-rigid object (or scene), observed from different viewpoints or even similar objects of the same class.

Luby Rackoff ciphers from weak round functions - Maurer, Ueli M; Oswald, Yvonne A; Krzysztof Pietrzak; Sjödin, Johan
The Feistel-network is a popular structure underlying many block-ciphers where the cipher is constructed from many simpler rounds, each defined by some function which is derived from the secret key. Luby and Rackoff showed that the three-round Feistel-network – each round instantiated with a pseudorandom function secure against adaptive chosen plaintext attacks (CPA) – is a CPA secure pseudorandom permutation, thus giving some confidence in the soundness of using a Feistel-network to design block-ciphers. But the round functions used in actual block-ciphers are – for efficiency reasons – far from being pseudorandom. We investigate the security of the Feistel-network against CPA distinguishers when the only security guarantee we have for the round functions is that they are secure against non-adaptive chosen plaintext attacks (nCPA). We show that in the information-theoretic setting, four rounds with nCPA secure round functions are sufficient (and necessary) to get a CPA secure permutation. Unfortunately, this result does not translate into the more interesting pseudorandom setting. In fact, under the so-called Inverse Decisional Diffie-Hellman assumption the Feistel-network with four rounds, each instantiated with a nCPA secure pseudorandom function, is in general not a CPA secure pseudorandom permutation.

Separating sources for encryption and secret sharing - Dodis, Yevgeniy; Krzysztof Pietrzak; Przydatek, Bartosz
Most cryptographic primitives such as encryption, authentication or secret sharing require randomness. Usually one assumes that perfect randomness is available, but those primitives might also be realized under weaker assumptions. In this work we continue the study of building secure cryptographic primitives from imperfect random sources initiated by Dodis and Spencer (FOCS’02). Their main result shows that there exists a (high-entropy) source of randomness allowing for perfect encryption of a bit, and yet from which one cannot extract even a single weakly random bit, separating encryption from extraction. Our main result separates encryption from 2-out-2 secret sharing (both in the information-theoretic and in the computational settings): any source which can be used to achieve one-bit encryption also can be used for 2-out-2 secret sharing of one bit, but the converse is false, even for high-entropy sources. Therefore, possibility of extraction strictly implies encryption, which in turn strictly implies 2-out-2 secret sharing.

Composition implies adaptive security in minicrypt - Krzysztof Pietrzak
To prove that a secure key-agreement protocol exists one must at least show P ≠NP. Moreover any proof that the sequential composition of two non-adaptively secure pseudorandom functions is secure against at least two adaptive queries must falsify the decisional Diffie-Hellman assumption, a standard assumption from public-key cryptography. Hence proving any of this two seemingly unrelated statements would require a significant breakthrough. We show that at least one of the two statements is true. To our knowledge this gives the first positive cryptographic result (namely that composition implies some weak adaptive security) which holds in Minicrypt, but not in Cryptomania, i.e. under the assumption that one-way functions exist, but public-key cryptography does not.

A tight bound for EMAC - Krzysztof Pietrzak
We prove a new upper bound on the advantage of any adversary for distinguishing the encrypted CBC-MAC (EMAC) based on random permutations from a random function. Our proof uses techniques recently introduced in [BPR05], which again were inspired by [DGH + 04]. The bound we prove is tight — in the sense that it matches the advantage of known attacks up to a constant factor — for a wide range of the parameters: let n denote the block-size, q the number of queries the adversary is allowed to make and ℓ an upper bound on the length (i.e. number of blocks) of the messages, then for ℓ ≤ 2 n/8 and q≥ł2 the advantage is in the order of q 2/2 n (and in particular independent of ℓ). This improves on the previous bound of q 2ℓΘ(1/ln ln ℓ)/2 n from [BPR05] and matches the trivial attack (which thus is basically optimal) where one simply asks random queries until a collision is found.

Place-selective firing of CA1 pyramidal cells during sharp wave/ripple network patterns in exploratory behavior - Joseph O'Neill; Senior,Timothy; Jozsef Csicsvari (Neuron)
We observed sharp wave/ripples (SWR) during exploration within brief (< 2.4 s) interruptions of or during theta oscillations. CA1 network responses of SWRs occurring during exploration (eSWR) and SWRs detected in waking immobility or sleep were similar. However, neuronal activity during eSWR was location dependent, and eSWR-related firing was stronger inside the place field than outside. The eSPW-related firing increase was stronger than the baseline increase inside compared to outside, suggesting a “supralinear” summation of eSWR and place-selective inputs. Pairs of cells with similar place fields and/or correlated firing during exploration showed stronger coactivation during eSWRs and subsequent sleep-SWRs. Sequential activation of place cells was not required for the reactivation of waking co-firing patterns; cell pairs with symmetrical cross-correlations still showed reactivated waking co-firing patterns during sleep-SWRs. We suggest that place-selective firing during eSWRs facilitates initial associations between cells with similar place fields that enable place-related ensemble patterns to recur during subsequent sleep-SWRs.

Will population bottlenecks and multilocus epistasis increase additive genetic variance? - Turelli, Michael; Nicholas Barton (Evolution; International Journal of Organic Evolution)
We apply new analytical methods to understand the consequences of population bottlenecks for expected additive genetic variance. We analyze essentially all models for multilocus epistasis that have been numerically simulated to demonstrate increased additive variance. We conclude that for biologically plausible models, large increases in expected additive variance–attributable to epistasis rather than dominance–are unlikely. Naciri-Graven and Goudet (2003) found that as the number of epistatically interacting loci increases, additive variance tends to be inflated more after a bottleneck. We argue that this result reflects biologically unrealistic aspects of their models. Specifically, as the number of loci increases, higher-order epistatic interactions become increasingly important in these models, with an increasing fraction of the genetic variance becoming nonadditive, contrary to empirical observations. As shown by Barton and Turelli (2004), without dominance, conversion of nonadditive to additive variance depends only on the variance components and not on the number of loci per se. Numerical results indicating that more inbreeding is needed to produce maximal release of additive variance with more loci follow directly from our analytical results, which show that high levels of inbreeding (F > 0.5) are needed for significant conversion of higher-order components. We discuss alternative approaches to modeling multilocus epistasis and understanding its consequences.

Objective quality measurement for geometric document image restoration - Christoph Lampert; Breuel,Thomas M
Many algorithms to remove distortion from document images have be proposed in recent years, but so far there is no reliable method for comparing their performance. In this paper we propose a collection of methods to measure the quality of such restoration algorithms for document image which show a non-linear distortion due to perspective or page curl. For the result from these measurement to be meaningful, a common data set of ground truth is required. We therefore started with the buildup of a document image database that is meant to serve as a common data basis for all kinds of restoration from images of 3D-shaped document. The long term goal would be to establish this database and following extensions in the area of document image dewarping as an as fruitful and indispensable tool as e.g. the NIST database is for OCR, or the Caltech database is for object and face recognition.

Machine learning for video compression: Macroblock mode decision - Christoph Lampert
Video compression currently is dominated by engineering and fine-tuned heuristic methods. In this paper, we propose to instead apply the well-developed machinery of machine learning in order to support the optimization of existing video encoders and the creation of new ones. Exemplarily, we show how by machine learning we can improve one encoding step that is crucial for the performance of all current video standards: macroblock mode decision. By formulating the problem in a Bayesian setup, we show that macroblock mode decision can be reduced to a classification problem with a cost function for misclassification that is sample dependent. We demonstrate how to apply different machine learning techniques to obtain suitable classifiers and we show in detailed experiments that all of these perform better than the state-of-the-art heuristic method

Protein expression enhancement in efflux-deleted mutant bacteria - Le,Thuc T.; Calin Guet; Cluzel,Philippe (Protein Expression and Purification)
We applied a single-cell assay to characterize how transcription dynamics affects protein expression levels of a tetracycline-inducible gene expression system. Transcriptional activity of the tetracycline promoter in response to a steady level of inducer is steady in ΔacrAB efflux mutant but pulsating in wildtype Escherichia coli cells. We found that the expression level of the green fluorescent protein is several folds higher in ΔacrAB efflux mutant than in wildtype cells.

Determinants of simulated RNA evolution. - Anne Kupczok; Dittrich,Peter (Journal of Theoretical Biology)
Models of RNA secondary structure folding are widely used to study evolution in theory and simulation. However, systematic studies of the parameters involved are rare. In this paper, we study by simulation how RNA evolution is influenced by three different factors, namely the mutation rate, scaling of the fitness function, and distance measure. We found that for low mutation rates the qualitative evolutionary behavior is robust with respect to the scaling of the fitness function. For efficient mutation rates, which are close to the error threshold, scaling and distance measure have a strong influence on the evolutionary behavior. A global distance measure that takes sequence information additively into account lowers the error threshold. When using a local sequence-structure alignment for the distance, we observed a smoother evolution of the fitness over time. Finally, in addition to the well known error threshold, we identify another threshold of the mutation rate, called divergence threshold, where the qualitative transient behavior changes from a localized to an exploratory search.

Hyperpolarization-activated cation channels in fast-spiking interneurons of rat hippocampus - Aponte, Yexica; Lien, Cheng-Chang; Reisinger, Ellen; Peter Jonas (Journal of Physiology)
Hyperpolarization-activated channels (Ih or HCN channels) are widely expressed in principal neurons in the central nervous system. However, Ih in inhibitory GABAergic interneurons is less well characterized. We examined the functional properties of Ih in fast-spiking basket cells (BCs) of the dentate gyrus, using hippocampal slices from 17- to 21-day-old rats. Bath application of the Ih channel blocker ZD 7288 at a concentration of 30 microm induced a hyperpolarization of 5.7 +/- 1.5 mV, an increase in input resistance and a correlated increase in apparent membrane time constant. ZD 7288 blocked a hyperpolarization-activated current in a concentration-dependent manner (IC50, 1.4 microm). The effects of ZD 7288 were mimicked by external Cs+. The reversal potential of Ih was -27.4 mV, corresponding to a Na+ to K+ permeability ratio (PNa/PK) of 0.36. The midpoint potential of the activation curve of Ih was -83.9 mV, and the activation time constant at -120 mV was 190 ms. Single-cell expression analysis using reverse transcription followed by quantitative polymerase chain reaction revealed that BCs coexpress HCN1 and HCN2 subunit mRNA, suggesting the formation of heteromeric HCN1/2 channels. ZD 7288 increased the current threshold for evoking antidromic action potentials by extracellular stimulation, consistent with the expression of Ih in BC axons. Finally, ZD 7288 decreased the frequency of miniature inhibitory postsynaptic currents (mIPSCs) in hippocampal granule cells, the main target cells of BCs, to 70 +/- 4% of the control value. In contrast, the amplitude of mIPSCs was unchanged, consistent with the presence of Ih in inhibitory terminals. In conclusion, our results suggest that Ih channels are expressed in the somatodendritic region, axon and presynaptic elements of fast-spiking BCs in the hippocampus.

Synapses formed by normal and abnormal hippocampal mossy fibers (Review) - Frotscher, Michael; Peter Jonas; Sloviter, Robert S (Cell and Tissue Research)
The axon terminals (mossy fibers) of hippocampal dentate granule cells form characteristic synaptic connections with large spines or excrescences of both hilar mossy cells and CA3 pyramidal neurons. Interneurons of the hilar region and area CA3 are also prominent targets of mossy fibers. The tracing of biocytin-filled mossy fibers and immunolabeling of target cells with interneuron markers has revealed that the majority of mossy fiber synapses project to gamma aminobutyric acid (GABA)-ergic inhibitory interneurons rather than to excitatory principal cells, although the functional implications of these quantitative differences are unclear. Following a brief description of the "classical" mossy fiber synapse on excrescences of CA3 pyramidal cells, the present review focuses on the contacts formed between granule cells and GABAergic interneurons, both normally and after synaptic reorganization. In response to deafferentation of mossy cell target cells, which include both granule cells and interneurons, mossy fibers "sprout" new axon collaterals that form a band of supragranular mossy fibers in the inner molecular layer of the dentate gyrus. Although most newly formed recurrent mossy fibers establish synapses with granule cells, there is an apparently convergent input of new mossy fibers onto GABA-immunoreactive interneuron dendrites that traverse the inner molecular layer. These mossy fiber-interneuron synapses in the dentate gyrus are observed in chronically epileptic rats and may be the structural correlate of the granule cell hyperinhibition observed in these animals in vivo. Together, the findings reviewed here establish mossy fiber synapses as an important component of inhibitory circuits in the hippocampus.

Timing and efficacy of transmitter release at mossy fiber synapses in the hippocampal network - Bischofberger, Josef; Engel, Dominique; Frotscher, Michael; Peter Jonas (Pflugers Archiv : European Journal of Physiology)
It is widely accepted that the hippocampus plays a major role in learning and memory. The mossy fiber synapse between granule cells in the dentate gyrus and pyramidal neurons in the CA3 region is a key component of the hippocampal trisynaptic circuit. Recent work, partially based on direct presynaptic patch-clamp recordings from hippocampal mossy fiber boutons, sheds light on the mechanisms of synaptic transmission and plasticity at mossy fiber synapses. A high Na(+) channel density in mossy fiber boutons leads to a large amplitude of the presynaptic action potential. Together with the fast gating of presynaptic Ca(2+) channels, this generates a large and brief presynaptic Ca(2+) influx, which can trigger transmitter release with high efficiency and temporal precision. The large number of release sites, the large size of the releasable pool of vesicles, and the huge extent of presynaptic plasticity confer unique strength to this synapse, suggesting a large impact onto the CA3 pyramidal cell network under specific behavioral conditions. The characteristic properties of the hippocampal mossy fiber synapse may be important for pattern separation and information storage in the dentate gyrus-CA3 cell network.

Shunting inhibition improves robustness of gamma oscillations in hippocampal interneuron networks by homogenizing firing rates - Vida, Imre; Bartos, Marlene; Peter Jonas (Neuron)
Networks of GABAergic neurons are key elements in the generation of gamma oscillations in the brain. Computational studies suggested that the emergence of coherent oscillations requires hyperpolarizing inhibition. Here, we show that GABA(A) receptor-mediated inhibition in mature interneurons of the hippocampal dentate gyrus is shunting rather than hyperpolarizing. Unexpectedly, when shunting inhibition is incorporated into a structured interneuron network model with fast and strong synapses, coherent oscillations emerge. In comparison to hyperpolarizing inhibition, networks with shunting inhibition show several advantages. First, oscillations are generated with smaller tonic excitatory drive. Second, network frequencies are tuned to the gamma band. Finally, robustness against heterogeneity in the excitatory drive is markedly improved. In single interneurons, shunting inhibition shortens the interspike interval for low levels of drive but prolongs it for high levels, leading to homogenization of neuronal firing rates. Thus, shunting inhibition may confer increased robustness to gamma oscillations in the brain.

The most important recent advances in synapse research from my point of view--and what remains to be done - Frotscher, Michael; Gundelfinger, Eckart; Peter Jonas; Neher, Erwin; Seeburg, Peter (Cell and Tissue Research)

Attack of the invasive garden ant: aggression behaviour of Lasius neglectus (Hymenoptera: Formicidae) against native Lasius species in Spain - Cremer, Sylvia; Ugelvig, Line V; Lommen, Suzanne; Petersen, Klaus; Pedersen, Jes (Myrmecological News)
Invasive species often dramatically change native species communities by directly and indirectly out-competing native species. We studied the direct interference abilities of the invasive garden ant, Lasius neglectus VAN LOON, BOOMSMA & ANDRÁSFALVY, 1990, by performing one-to-one aggression tests of L. neglectus workers towards three native Lasius ant species that occur at the edge of a L. neglectus supercolony in Seva, Spain. Our results show that L. neglectus is highly aggressive against all three native Lasius species tested (L. grandis FOREL, 1909, L. emarginatus (OLIVIER, 1792), and L. cinereus SEIFERT, 1992), expressed as a higher attack rate of L. neglectus and behavioural dominance throughout the aggressive encounters. Attacks of L. neglectus were performed fastest and most frequent against L. grandis, and also the highest antennation frequencies were observed in encounters between these two species. This could be due to the largest difference in body size, or due to a greater overlap in ecological niche between L. neglectus and L. grandis compared to the other two native species. There was only weak support for L. neglectus workers from the periphery of the supercolony to be more aggressive relative to workers from the centre, even though the former encounter native ant species on a daily basis at the edge of the supercolony.

Optimal species distinction by discriminant analysis: comparing established methods of character selection with a combination procedure using ant morphometrics as a case study - Moder, Karl; Schlick Steiner, Birgit; Steiner, Florian; Cremer, Sylvia; Christian, Erhard; Seifert, Bernhard (Journal of Zoological Systematics and Evolutionary Research)
We compare the performances of established means of character selection for discriminant analysis in species distinction with a combination procedure for finding the optimal character combination (minimum classification error, minimum number of required characters), using morphometric data sets from the ant genera Cardiocondyla, Lasius and Tetramorium. The established methods are empirical character selection as well as forward selection, backward elimination and stepwise selection of discriminant analysis. The combination procedure is clearly superior to the established methods of character selection, and is widely applicable.

Stealthy invaders: the biology of Cardiocondyla tramp ants - Heinze, Jürgen; Cremer, Sylvia; Eckl, Norbert; Schrempf, Alexandra (Insectes Sociaux)
Many invasive ant species, such as the Argentine ant or the red imported fire ant, have huge colonies with thousands of mass-foraging workers, which quickly monopolise resources and therefore represent a considerable threat to the native ant fauna. Cardiocondyla obscurior and several other species of this myrmicine genus have similarly been transferred throughout the tropics by human activities. However, because their colonies are tiny and workers forage solitarily, Cardiocondyla are often not recognized as successful invaders. Here, we document that the life history of Cardiocondyla closely resembles that of the more conspicuous tramp species, with polygyny, intranidal mating, budding, worker sterility, low genetic variability, and possibly also unicoloniality. Given that introduced Cardiocondyla may locally reach a very high population density, the effects of these stealthy invaders on the native arthropod fauna should receive more attention.

EGF-stimulated migration in ovarian cancer cells is associated with decreased internalization, increased surface expression, and increased shedding of the urokinase plasminogen activator receptor - Henic, Emir; Michael Sixt; Hansson, Stefan; Høyer-Hansen, Gunilla; Casslén, Bertil (Gynecologic Oncology)
OBJECTIVES: The EGFR is expressed in malignant ovarian tumor tissue, and tissue content of EGFR has been directly associated with poor prognosis in patients with ovarian cancer. The uPA system plays a role in pericellular proteolysis, cell migration, invasion, and is over-expressed in ovarian cancer. This study explored the effects of EGF on uPAR expression in the ovarian cancer cell line OVCAR-3. METHODS: We used OVCAR-3 cells and the following methods: cell migration assay, time-lapse video microscopy, real-time PCR, assays for cellular binding of 125I-uPA and cellular degradation of 125I-uPA:PAI-1 complex, biosynthetic labeling using 35S-methionin, Western blot, Northern blot, and ELISAs for uPA, PAI-1, and uPAR. RESULTS: EGF up-regulates both protein and mRNA not only for uPAR, but also for the ligand uPA and its inhibitor PAI-1. Cell surface uPAR, in control as well as EGF-stimulated cells, is present only in the intact, not the cleaved, form. Ligand binding experiments showed an increase of endogenously occupied uPAR, whereas non-occupied receptor sites were not increased. In addition, EGF treatment resulted in decreased degradation of radiolabeled uPA:PAI-1 complex. This suggests decreased internalization of uPAR, since the complex is internalized together with uPAR. Like EGF, colchicine, which inhibits endocytosis, increased cell surface expression of uPAR. In addition, we found an immediate increase of uPAR after exposing the cells to EGF and this was accompanied by a transient increase of cell migration. The increase of cell surface uPAR in response to EGF is accompanied by increased release of the soluble form of uPAR (suPAR) to the medium as well as by increased cell migration. Both uPAR and suPAR increased in cells treated with the endocytosis inhibitor colchicine even though cell migration was inhibited, suggesting that the mechanism of uPAR shedding is not related to cell migration. CONCLUSION: Increased cell surface uPAR in response to EGF stimulation results from mobilization of uPAR from detergent-resistant domains, increased expression of uPAR mRNA, and decreased internalization and degradation of uPAR. Both the anti-uPAR antibody R3, which inhibits binding of uPA, and the EGFR phosphorylation inhibitor Iressa inhibited cell migration in response to uPA as well as to EGF, suggesting that EGFR and uPAR are engaged in the same multiprotein assembly on the cell surface.

Evaluating the quality of NMR structures by local density of protons - Ban, Yih-En Andrew; Rudolph, Johannes; Zhou, Pei; Herbert Edelsbrunner (Proteins: Structure, Function and Bioinformatics)
Evaluating the quality of experimentally determined protein structural models is an essential step toward identifying potential errors and guiding further structural refinement. Herein, we report the use of proton local density as a sensitive measure to assess the quality of nuclear magnetic resonance (NMR) structures. Using 256 high-resolution crystal structures with protons added and optimized, we show that the local density of different proton types display distinct distributions. These distributions can be characterized by statistical moments and are used to establish local density Z-scores for evaluating both global and local packing for individual protons. Analysis of 546 crystal structures at various resolutions shows that the local density Z-scores increase as the structural resolution decreases and correlate well with the ClashScore (Word et al. J Mol Biol 1999;285(4):1711-1733) generated by all atom contact analysis. Local density Z-scores for NMR structures exhibit a significantly wider range of values than for X-ray structures and demonstrate a combination of potentially problematic inflation and compression. Water-refined NMR structures show improved packing quality. Our analysis of a high-quality structural ensemble of ubiquitin refined against order parameters shows proton density distributions that correlate nearly perfectly with our standards derived from crystal structures, further validating our approach. We present an automated analysis and visualization tool for proton packing to evaluate the quality of NMR structures.

Interface surfaces for protein-protein complexes - Ban, Yih-En Andrew; Herbert Edelsbrunner; Rudolph, Johannes (Journal of the ACM)
Protein-protein interactions, which form the basis for most cellular processes, result in the formation of protein interfaces. Believing that the local shape of proteins is crucial, we take a geometric approach and present a definition of an interface surface formed by two or more proteins as a subset of their Voronoi diagram. The definition deals with the difficult and important problem of specifying interface boundaries by invoking methods used in the alpha shape representation of molecules, the discrete flow on Delaunay simplices to define pockets and reconstruct surfaces, and the assessment of the importance of topological features. We present an algorithm to construct the surface and define a hierarchy that distinguishes core and peripheral regions. This hierarchy is shown to have correlation with hot-spots in protein-protein interactions. Finally, we study the geometric and topological properties of interface surfaces and show their high degree of contortion.

Extreme elevation on a 2-manifold - Agarwal, Pankaj K; Herbert Edelsbrunner; Harer, John; Wang, Yusu (Discrete & Computational Geometry)
Given a smoothly embedded 2-manifold in R-3, we define the elevation of a point as the height difference to a canonically defined second point on the same manifold. Our definition is invariant under rigid motions and can be used to define features such as lines of discontinuous or continuous but non-smooth elevation. We give an algorithm for finding points of locally maximum elevation, which we suggest mark cavities and protrusions and are useful in matching shapes as for example in protein docking.

Bibliothek 2.0 - Die Bibliothek der Zukunft? - Patrick Danowski; Heller,Lambert (Bibliotheksdienst)
Der Artikel beschäftigt sich mit dem Konzept der Bibliothek 2.0 (bzw. Library 2.0). Er skizziert anhand einiger Beispiele die Entwicklung zum Web 2.0 und beschreibt, wie Web 2.0-Technologien und -Anwendungen in Bibliotheken eingesetzt werden. Im Mittelpunkt stehen Social-Tagging-Systeme, benutzerorientierte Erweiterungen von Bibliothekskatalogen und Dokumentenservern sowie der Einsatz von Weblogs an Bibliotheken. Ferner werden neue Anforderungen an Bibliothekare diskutiert.

Population structure of the malaria vector Anopheles darlingi in a malaria-endemic region of eastern Amazonian Brazil - Conn, Jan E; Vineis, Joseph H; Jonathan Bollback; Onyabe, David Y; Wilkerson, Richard C; Povoa, Marinete M (The American Journal of Tropical Medicine and Hygiene)
Anopheles darlingi is the primary malaria vector in Latin America, and is especially important in Amazonian Brazil. Historically, control efforts have been focused on indoor house spraying using a variety of insecticides, but since the mid-1990s there has been a shift to patient treatment and focal insecticide fogging. Anopheles darlingi was believed to have been significantly reduced in a gold-mining community, Peixoto de Azevedo (in Mato Grosso State), in the early 1990s by insecticide use during a severe malaria epidemic. In contrast, although An. darlingi was eradicated from some districts of the city of Belem (the capital of Para State) in 1968 to reduce malaria, populations around the water protection area in the eastern district were treated only briefly. To investigate the population structure of An. darlingi including evidence for a population bottleneck in Peixoto, we analyzed eight microsatellite loci of 256 individuals from seven locations in Brazil: three in Amapa State, three in Para State, and one in Mato Grosso State. Allelic diversity and mean expected heterozygosity were high for all populations (mean number alleles/locus and H(E) were 13.5 and 0.834, respectively) and did not differ significantly between locations. Significant heterozygote deficits were associated with linkage disequilibrium, most likely due to either the Wahlund effect or selection. We found no evidence for a population bottleneck in Peixoto, possibly because the reduction was not extreme enough to be detected. Overall estimates of long-term N(e) varied from 92.4 individuals under the linkage disequilibrium model to infinity under the heterozygote excess model. Fixation indices and analysis of molecular variance demonstrated significant differentiation between locations north and south of the Amazon River, suggesting a degree of genetic isolation between them, attributed to isolation by distance.

SIMMAP: stochastic character mapping of discrete traits on phylogenies - Jonathan Bollback (BMC Bioinformatics)
BACKGROUND: Character mapping on phylogenies has played an important, if not critical role, in our understanding of molecular, morphological, and behavioral evolution. Until very recently we have relied on parsimony to infer character changes. Parsimony has a number of serious limitations that are drawbacks to our understanding. Recent statistical methods have been developed that free us from these limitations enabling us to overcome the problems of parsimony by accommodating uncertainty in evolutionary time, ancestral states, and the phylogeny. RESULTS: SIMMAP has been developed to implement stochastic character mapping that is useful to both molecular evolutionists, systematists, and bioinformaticians. Researchers can address questions about positive selection, patterns of amino acid substitution, character association, and patterns of morphological evolution. CONCLUSION: Stochastic character mapping, as implemented in the SIMMAP software, enables users to address questions that require mapping characters onto phylogenies using a probabilistic approach that does not rely on parsimony. Analyses can be performed using a fully Bayesian approach that is not reliant on considering a single topology, set of substitution model parameters, or reconstruction of ancestral states. Uncertainty in these quantities is accommodated by using MCMC samples from their respective posterior distributions.

A comparative study of energy minimization methods for Markov random fields - Szeliski, Richard S; Zabih, Ramin; Scharstein, Daniel; Veksler, Olga; Vladimir Kolmogorov; Agarwala, Aseem; Tappen, Marshall F; Rother, Carsten
One of the most exciting advances in early vision has been the development of efficient energy minimization algorithms. Many early vision tasks require labeling each pixel with some quantity such as depth or texture. While many such problems can be elegantly expressed in the language of Markov Random Fields (MRF's), the resulting energy minimization problems were widely viewed as intractable. Recently, algorithms such as graph cuts and loopy belief propagation (LBP) have proven to be very powerful: for example, such methods form the basis for almost all the top-performing stereo methods. Unfortunately, most papers define their own energy function, which is minimized with a specific algorithm of their choice. As a result, the tradeoffs among different energy minimization algorithms are not well understood. In this paper we describe a set of energy minimization benchmarks, which we use to compare the solution quality and running time of several common energy minimization algorithms. We investigate three promising recent methods - graph cuts, LBP, and tree-reweighted message passing - as well as the well-known older iterated conditional modes (ICM) algorithm. Our benchmark problems are drawn from published energy functions used for stereo, image stitching and interactive segmentation. We also provide a general-purpose software interface that allows vision researchers to easily switch between optimization methods with minimal overhead. We expect that the availability of our benchmarks and interface will make it significantly easier for vision researchers to adopt the best method for their specific problems. Benchmarks, code, results and images are available at http://vision.middlebury.edu/MRF.

Comparison of energy minimization algorithms for highly connected graphs - Vladimir Kolmogorov; Rother, Carsten
Algorithms for discrete energy minimization play a fundamental role for low-level vision. Known techniques include graph cuts, belief propagation (BP) and recently introduced tree-reweighted message passing (TRW). So far, the standard benchmark for their comparison has been a 4-connected grid-graph arising in pixel-labelling stereo. This minimization problem, however, has been largely solved: recent work shows that for many scenes TRW finds the global optimum. Furthermore, it is known that a 4-connecled grid-graph is a poor stereo model since it does not take occlusions into account. We propose the problem of stereo with occlusions as a new test bed for minimization algorithms. This is a more challenging graph since it has much larger connectivity, and it also serves as a better stereo model. An attractive feature of this problem is that increased connectivity does not result in increased complexity of message passing algorithms. Indeed, one contribution of this paper is to show that sophisticated implementations of BP and TRW have the same time and memory complexity as that of 4-connecled grid-graph stereo. The main conclusion of our experimental study is that for our problem graph cut outperforms both TRW and BP considerably. TRW achieves consistently a lower energy than BP. However, as connectivity increases the speed of convergence of TRW becomes slower. Unlike 4-connected grids, the difference between the energy of the best optimization method and the lower bound of TRW appears significant. This shows the hardness of the problem and motivates future research.

Probabilistic fusion of stereo with color and contrast for bilayer segmentation - Vladimir Kolmogorov; Criminisi, Antonio; Blake, Andrew; Cross, Geoffrey; Rother, Carsten (IEEE Transactions on Pattern Analysis and Machine Intelligence)
This paper describes models and algorithms for the real-time segmentation of foreground from background layers in stereo video sequences. Automatic separation of layers from color/contrast or from stereo alone is known to be error-prone. Here, color, contrast, and stereo matching information are fused to infer layers accurately and efficiently. The first algorithm, Layered Dynamic Programming (LDP), solves stereo in an extended six-state space that represents both foreground/background layers and occluded regions. The stereo-match likelihood is then fused with a contrast-sensitive color model that is learned on-the-fly and stereo disparities are obtained by dynamic programming. The second algorithm, Layered Graph Cut (LGC), does not directly solve stereo. Instead, the stereo match likelihood is marginalized over disparities to evaluate foreground and background hypotheses and then fused with a contrast-sensitive color model like the one used in LDP. Segmentation is solved efficiently by ternary graph cut. Both algorithms are evaluated with respect to ground truth data and found to have similar performance, substantially better than either stereo or color/contrast alone. However, their characteristics with respect to computational efficiency are rather different. The algorithms are demonstrated in the application of background substitution and shown to give good quality composite video output.

An integral solution to surface evolution PDEs via geo cuts - Boykov, Yuri; Vladimir Kolmogorov; Cremers, Daniel; Delong, Andrew
We introduce a new approach to modelling gradient flows of contours and surfaces. While standard variational methods (e.g. level sets) compute local interface motion in a differential fashion by estimating local contour velocity via energy derivatives, we propose to solve surface evolution PDEs by explicitly estimating integral motion of the whole surface. We formulate an optimization problem directly based on an integral characterization of gradient flow as an infinitesimal move of the (whole) surface giving the largest energy decrease among all moves of equal size. We show that this problem can be efficiently solved using recent advances in algorithms for global hypersurface optimization [4, 2, 11]. In particular, we employ the geo-cuts method [4] that uses ideas from integral geometry to represent continuous surfaces as cuts on discrete graphs. The resulting interface evolution algorithm is validated on some 2D and 3D examples similar to typical demonstrations of level-set methods. Our method can compute gradient flows of hypersurfaces with respect to a fairly general class of continuous functional and it is flexible with respect to distance metrics on the space of contours/surfaces. Preliminary tests for standard L2 distance metric demonstrate numerical stability, topological changes and an absence of any oscillatory motion.

Atomic force microscopy - Harald Janovjak; Sawhney, Ravi K; Stark, Martin; Mueller, Daniel J (Techniques in Microscopy for Biomedical Applications)

Bacteriorhodopsin folds into the membrane against an external force - Kessler, Max; Gottschalk, Kay E; Harald Janovjak; Mueller, Daniel J; Gaub, Hermann (Journal of Molecular Biology)
Despite their crucial importance for cellular function, little is known about the folding mechanisms of membrane proteins. Recently details of the folding energy landscape were elucidated by atomic force microscope (AFM)-based single molecule force spectroscopy. Upon unfolding and extraction of individual membrane proteins energy barriers in structural elements such as loops and helices were mapped and quantified with the precision of a few amino acids. Here we report on the next logical step: controlled refolding of single proteins into the membrane. First individual bacteriorhodopsin monomers were partially unfolded and extracted from the purple membrane by pulling at the C-terminal end with an AFM tip. Then by gradually lowering the tip, the protein was allowed to refold into the membrane while the folding force was recorded. We discovered that upon refolding certain helices are pulled into the membraneagainst a sizable externalforce of several tens of picoNewton. From the mechanical work, which the helix performs on the AFM cantilever, we derive an upper limit for the Gibbs free folding energy. Subsequent unfolding allowed us to analyze the pattern of unfolding barriers and corroborate that the protein had refolded into the native state.

Observing folding pathways and kinetics of a single sodium-proton antiporter from Escherichia coli - Kedrov, Alexej; Harald Janovjak; Ziegler, Christine; Kühlbrandt, Werner; Mueller, Daniel J (Journal of Molecular Biology)
Mechanisms of folding and misfolding of membrane proteins are of interest in cell biology. Recently, we have established single-molecule force spectroscopy to observe directly the stepwise folding of the Na+/H+antiporter NhaA from Escherichia coli in vitro. Here, we improved this approach significantly to track the folding intermediates of asingle NhaA polypeptide forming structural segments such as the Na+-binding site, transmembrane α-helices, and helical pairs. The folding rates of structural segments ranged from 0.31 s−1 to 47 s−1, providing detailed insight into a distinct folding hierarchy of an unfolded polypeptide into the native membrane protein structure. In some cases, however, the folding chain formed stable and kinetically trapped non-native structures, which could be assigned to misfolding events of the antiporter.

Imaging and detecting molecular interactions of single membrane proteins - Harald Janovjak; Kedrov, Alexej; Cisneros, David; Sapra, Tanuj K; Struckmeier, Jens; Mueller, Daniel J (Neurobiology of Aging)

Fitness effects of beneficial mutations: the mutational landscape model in experimental evolution - Betancourt, Andrea J; Jonathan Bollback (Current Opinion in Genetics & Development)
The mutational landscape model is a theoretical model describing sequence evolution in natural populations. However, recent experimental work has begun to test its predictions in laboratory populations of microbes. Several of these studies have focused on testing the prediction that the effects of beneficial mutations should be roughly exponentially distributed. The prediction appears to be borne out by most of these studies, at least qualitatively. Another study showed that a modified version of the model was able to predict, with reasonable accuracy, which of a ranked set of beneficial alleles will be fixed next. Although it remains to be seen whether the mutational landscape model adequately describes adaptation in organisms other than microbes, together these studies suggest that adaptive evolution has surprisingly general properties that can be successfully captured by theoretical models.

Ising models for networks of real neurons - Gasper Tkacik; Schneidman, E.; Berry, M. J.; Bialek, William S (ArXiv)
Ising models with pairwise interactions are the least structured, or maximum-entropy, probability distributions that exactly reproduce measured pairwise correlations between spins. Here we use this equivalence to construct Ising models that describe the correlated spiking activity of populations of 40 neurons in the retina, and show that pairwise interactions account for observed higher-order correlations. By first finding a representative ensemble for observed networks we can create synthetic networks of 120 neurons, and find that with increasing size the networks operate closer to a critical point and start exhibiting collective behaviors reminiscent of spin glasses.

Games for controls - Krishnendu Chatterjee; Jagadeesan, Rhada; Pitcher, Corin
We argue that games are expressive enough to encompass (history-based) access control, (resource) usage control (e.g., dynamic adaptive access control of reputation systems), accountability based controls (e.g., insurance), controls derived from rationality assumptions on participants (e.g., network mechanisms), and their composition. Building on the extensive research into games, we demonstrate that this expressive power coexists with a formal analysis framework comparable to that available for access control.

Timing and efficacy of transmitter release at mossy fiber synapses in the hippocampal network. (Review) - Bischofberger, Joseph; Engel, Dominique; Frotscher, Michael; Peter Jonas (Pflugers Archiv : European Journal of Physiology)
It is widely accepted that the hippocampus plays a major role in learning and memory. The mossy fiber synapse between granule cells in the dentate gyrus and pyramidal neurons in the CA3 region is a key component of the hippocampal trisynaptic circuit. Recent work, partially based on direct presynaptic patch-clamp recordings from hippocampal mossy fiber boutons, sheds light on the mechanisms of synaptic transmission and plasticity at mossy fiber synapses. A high Na(+) channel density in mossy fiber boutons leads to a large amplitude of the presynaptic action potential. Together with the fast gating of presynaptic Ca(2+) channels, this generates a large and brief presynaptic Ca(2+) influx, which can trigger transmitter release with high efficiency and temporal precision. The large number of release sites, the large size of the releasable pool of vesicles, and the huge extent of presynaptic plasticity confer unique strength to this synapse, suggesting a large impact onto the CA3 pyramidal cell network under specific behavioral conditions. The characteristic properties of the hippocampal mossy fiber synapse may be important for pattern separation and information storage in the dentate gyrus-CA3 cell network.

Nash equilibrium for upward-closed objectives - Krishnendu Chatterjee
We study infinite stochastic games played by n-players on a finite graph with goals specified by sets of infinite traces. The games are concurrent (each player simultaneously and independently chooses an action at each round), stochastic (the next state is determined by a probability distribution depending on the current state and the chosen actions), infinite (the game continues for an infinite number of rounds), nonzero-sum (the players’ goals are not necessarily conflicting), and undiscounted. We show that if each player has an upward-closed objective, then there exists an ε-Nash equilibrium in memoryless strategies, for every ε>0; and exact Nash equilibria need not exist. Upward-closure of an objective means that if a set Z of infinitely repeating states is winning, then all supersets of Z of infinitely repeating states are also winning. Memoryless strategies are strategies that are independent of history of plays and depend only on the current state. We also study the complexity of finding values (payoff profile) of an ε-Nash equilibrium. We show that the values of an ε-Nash equilibrium in nonzero-sum concurrent games with upward-closed objectives for all players can be computed by computing ε-Nash equilibrium values of nonzero-sum concurrent games with reachability objectives for all players and a polynomial procedure. As a consequence we establish that values of an ε-Nash equilibrium can be computed in TFNP (total functional NP), and hence in EXPTIME.

Algorithms for Büchi Games - Krishnendu Chatterjee; Thomas Henzinger; Piterman, Nir
The classical algorithm for solving Bu ̈chi games requires time O(n · m) for game graphs with n states and m edges. For game graphs with constant outdegree, the best known algorithm has running time O(n2/logn). We present two new algorithms for Bu ̈chi games. First, we give an algorithm that performs at most O(m) more work than the classical algorithm, but runs in time O(n) on infinitely many graphs of constant outdegree on which the classical algorithm requires time O(n2). Second, we give an algorithm with running time O(n · m · log δ(n)/ log n), where 1 ≤ δ(n) ≤ n is the outdegree of the game graph. Note that this algorithm performs asymptotically better than the classical algorithm if δ(n) = O(log n).

Method, apparatus and computer program products for automatically generating NURBS models of triangulated surfaces using homeomorphism - Edelsbrunner, Herbert; Fu, Ping; Nekhayev, Dmitry; Facello, Michael; Williams, Steven
Embodiments automatically generate an accurate network of watertight NURBS patches from polygonal models of objects while automatically detecting and preserving character lines thereon. These embodiments generate from an initial triangulation of the surface, a hierarchy of progressively coarser triangulations of the surface by performing a sequence of edge contractions using a greedy algorithm that selects edge contractions by their numerical properties. Operations are also performed to connect the triangulations in the hierarchy using homeomorphisms that preserve the topology of the initial triangulation in the coarsest triangulation. A desired quadrangulation of the surface can then be generated by homeomorphically mapping edges of a coarsest triangulation in the hierarchy back to the initial triangulation. This quadrangulation is topologically consistent with the initial triangulation and is defined by a plurality of quadrangular patches. These quadrangular patches are linked together by a (U, V) mesh that is guaranteed to be continuous at patch boundaries. A grid is then preferably fit to each of the quadrangles in the resulting quadrangulation by decomposing each of the quadrangles into k.sup.2 smaller quadrangles. A watertight NURBS model may be generated from the resulting quadrangulation.

Manufacturing methods and systems for rapid production of hearing-aid shells - Fu, Ping; Nekhayev, Dmitry; Edelsbrunner, Herbert
Methods, apparatus and computer program products provide efficient techniques for designing and printing shells of hearing-aid devices with a high degree of quality assurance and reliability and with a reduced number of manual and time consuming production steps and operations. These techniques also preferably provide hearing-aid shells having internal volumes that can approach a maximum allowable ratio of internal volume relative to external volume. These high internal volumes facilitate the inclusion of hearing-aid electrical components having higher degrees of functionality and/or the use of smaller and less conspicuous hearing-aid shells. A preferred method includes operations to generate a watertight digital model of a hearing-aid shell by thickening a three-dimensional digital model of a shell surface in a manner that eliminates self-intersections and results in a thickened model having an internal volume that is a high percentage of an external volume of the model.

Method, apparatus and computer products that reconstruct surfaces from data points - Fletcher, Yates; Gloth, Tobias; Edelsbrunner, Herbert; Fu, Ping
Methods, apparatus and computer program products provide efficient techniques for reconstructing surfaces from data point sets. These techniques include reconstructing surfaces from sets of scanned data points that have preferably undergone preprocessing operations to improve their quality by, for example, reducing noise and removing outliers. These techniques include reconstructing a dense and locally two-dimensionally distributed 3D point set (e.g., point cloud) by merging stars in two-dimensional weighted Delaunay triangulations within estimated tangent planes. The techniques include determining a plurality of stars from a plurality of points p.sub.i in a 3D point set S that at least partially describes the 3D surface, by projecting the plurality of points p.sub.i onto planes T.sub.i that are each estimated to be tangent about a respective one of the plurality of points p.sub.i. The plurality of stars are then merged into a digital model of the 3D surface.

Changes in functional connectivity within the rat striatopallidal axis during global brain activation in vivo - Magill,Peter J; Pogosyan,Alek; Sharott,Andrew; Jozsef Csicsvari; Bolam, John Paul; Brown,Peter (Journal of Neuroscience)
The functional organization of the basal ganglia ( BG) is often defined according to one of two opposing schemes. The first proposes multiple, essentially independent channels of information processing. The second posits convergence and lateral integration of striatal channels at the level of the globus pallidus ( GP). We tested the hypothesis that these proposed aspects of functional connectivity within the striatopallidal axis are dynamic and related to brain state. Local field potentials ( LFPs) were simultaneously recorded from multiple sites in striatum and GP in anesthetized rats during slow-wave activity( SWA) and during global activation evoked by sensory stimulation. Functional connectivity was inferred from comparative analyses of the internuclear and intranuclear coherence between bipolar derivations of LFPs. During prominent SWA, as shown in the electrocorticogram and local field potentials in the basal ganglia, intranuclear coherence, and, thus, lateral functional connectivity within striatum or globus pallidus was relatively weak. Furthermore, the temporal coupling of LFPs recorded across these two nuclei involved functional convergence at the level of GP. Global activation, indicated by a loss of SWA, was accompanied by a rapid functional reorganization of the striatopallidal axis. Prominent lateral functional connectivity developed within GP and, to a significantly more constrained spatial extent, striatum. Additionally, functional convergence on GP was no longer apparent, despite increased internuclear coherence. These data demonstrate that functional connectivity within the BG is highly dynamic and suggest that the relative expression of organizational principles, such as parallel, independent processing channels, striatopallidal convergence, and lateral integration within BG nuclei, is dependent on brain state.

Vines and vineyards by updating persistence in linear time - Cohen-Steiner, David; Herbert Edelsbrunner; Morozov, Dmitriy
Persistent homology is the mathematical core of recent work on shape, including reconstruction, recognition, and matching. Its per- tinent information is encapsulated by a pairing of the critical values of a function, visualized by points forming a diagram in the plane. The original algorithm in [10] computes the pairs from an ordering of the simplices in a triangulation and takes worst-case time cubic in the number of simplices. The main result of this paper is an algorithm that maintains the pairing in worst-case linear time per transposition in the ordering. A side-effect of the algorithm’s anal- ysis is an elementary proof of the stability of persistence diagrams [7] in the special case of piecewise-linear functions. We use the algorithm to compute 1-parameter families of diagrams which we apply to the study of protein folding trajectories.

Persistence-sensitive simplification of functions on 2-manifolds - Herbert Edelsbrunner; Morozov, Dmitriy; Pascucci, Valerio
We continue the study of topological persistence [5] by investigat- ing the problem of simplifying a function f in a way that removes topological noise as determined by its persistence diagram [2]. To state our results, we call a function g an ε-simplification of another function f if ∥f − g∥∞ ≤ ε, and the persistence diagrams of g are the same as those of f except all points within L1-distance at most ε from the diagonal have been removed. We prove that for func- tions f on a 2-manifold such ε-simplification exists, and we give an algorithm to construct them in the piecewise linear case.

Hybridisation between red and sika deer in Scotland - Pemberton, Josephine M; Swanson, Graeme M; Nicholas Barton; Livingstone, Suzanne R; Senn, Helen V (Deer)

Hybridization of Bombina bombina and B. variegata (Anura, Discoglossidae) at a sharp ecotone in western Ukraine: comparisons across transects and over time - Yanchukov, Alexey; Hofman, Sebastian; Szymura, Jacek M; Mezhzherin, Sergey V; Morozov-Leonov, Sviatoslav; Nicholas Barton; Nürnberger, Beate (Evolution; International Journal of Organic Evolution)
Bombina bombina and B. variegata are two anciently diverged toad taxa that have adapted to different breeding habitats yet hybridize freely in zones of overlap where their parapatric distributions meet. Here, we report on a joint genetic and ecological analysis of a hybrid zone in the vicinity of Stryi in western Ukraine. We used five unlinked allozyme loci, two nuclear single nucleotide polymorphisms and a mitochondrial DNA haplotype as genetic markers. Parallel allele frequency clines with a sharp central step occur across a sharp ecotone, where transitions in aquatic habitat, elevation, and terrestrial vegetation coincide. The width of the hybrid zone, estimated as the inverse of the maximum gradient in allele frequency, is 2.3 km. This is the smallest of four estimates derived from different clinal transects across Europe. We argue that the narrow cline near Stryi is mainly due to a combination of habitat distribution and habitat preference. Adult toads show a preference for either ponds (B. bombina) or puddles (B. variegata), which is known to affect the distribution of genotypes within the hybrid zones. At Stryi, it should cause a reduction of the dispersal rate across the ecotone and thus narrow the cline. A detailed comparison of all five intensively studied Bombina transects lends support to the hypothesis that habitat distribution plus habitat preference can jointly affect the structure of hybrid zones and, ultimately, the resulting barriers to gene flow between differentiated gene pools. This study also represents a resampling of an area that was last studied more than 70 years ago. Our allele-frequency clines largely coincide with those that were described then on the basis of morphological variation. However, we found asymmetrical introgression of B. variegata genes into B. bombina territory along the bank of a river.

Chromosome inversions, local adaptation, and speciation - Kirkpatrick, Mark; Nicholas Barton (Genetics)
We study the evolution of inversions that capture locally adapted alleles when two populations are exchanging migrants or hybridizing. By suppressing recombination between the loci, a new inversion can spread. Neither drift nor coadaptation between the alleles (epistasis) is needed, so this local adaptation mechanism may apply to a broader range of genetic and demographic situations than alternative hypotheses that have been widely discussed. The mechanism can explain many features observed in inversion systems. It will drive an inversion to high frequency if there is no countervailing force, which could explain fixed differences observed between populations and species. An inversion can be stabilized at an intermediate frequency if it also happens to capture one or more deleterious recessive mutations, which could explain polymorphisms that are common in some species. This polymorphism can cycle in frequency with the changing selective advantage of the locally favored alleles. The mechanism can establish underdominant inversions that decrease heterokaryotype fitness by several percent if the cause of fitness loss is structural, while if the cause is genic there is no limit to the strength of underdominance that can result. The mechanism is expected to cause loci responsible for adaptive species-specific differences to map to inversions, as seen in recent QTL studies. We discuss data that support the hypothesis, review other mechanisms for inversion evolution, and suggest possible tests.

Prediction of effects of genetic drift on variance components under a general model of epistasis - Hill, William G; Nicholas Barton; Turelli, Michael (Theoretical Population Biology)
For a model of diallelic loci with arbitrary epistasis, Barton and Turelli [2004. Effects of genetic drift on variance components under a general model of epistasis. Evolution 58, 2111–2132] gave results for variances among and within replicate lines obtained by inbreeding without selection. Here, we discuss the relation between their population genetic methods and classical quantitative genetic arguments. In particular, we consider the case of no dominance using classical identity by descent arguments, which generalizes their results from two alleles to multiple alleles. To clarify the connections between the alternative methods, we obtain the same results using an intermediate method, which explicitly identifies the statistical effects of sets of loci. We also discuss the effects of population bottlenecks on covariances among relatives.

Satellite tracks removal in astronomical images - Ali,Haider; Christoph Lampert; Breuel,Thomas M
This paper describes a new system for "Finding Satellite Tracks” in astronomical images based on the modern geometric approach. There is an increasing need of using methods with solid mathematical and statistical foundation in astronomical image processing. Where the computational methods are serving in all disciplines of science, they are becoming popular in the field of astronomy as well. Currently different computational systems are required to be numerically optimized before to get applied on astronomical images. So at present there is no single system which solves the problems of astronomers using computational methods based on modern approaches. The system "Finding Satellite Tracks” is based on geometric matching method "Recognition by Adaptive Subdivision of Transformation Space (RAST)".

Spatiogram-based shot distances for video retrieval - Ulges, Adrian; Christoph Lampert; Keysers,Daniel
We propose a video retrieval framework based on a novel combination of spatiograms and the Jensen-Shannon divergence, and validate its performance in two quantitative experiments on TRECVID BBC Rushes data. In the first experiment, color-based methods are tested by grouping redundant shots in an unsupervised clustering. Results of the second experiment show that motion-based spatiograms make a promising fast, compressed-domain descriptor for the detection of interview scenes.

Printing technique classification for document counterfeit detection - Christoph Lampert; Mei,Lin; Breuel,Thomas M
The detection of counterfeit in printed documents is currently based mainly on built-in security features or on human expertise. We propose a classification system that supports non-expert users to distinguish original documents from PC-made forgeries by analyzing the printing technique used. Each letter in a document is classified using a support vector machine that has been trained to distinguish laser from inkjet printouts. A color-coded visualization helps the user to interpret the per-letter classification results